PENGGUNAAN MATERIAL LOGAM DI BERBAGAI INDUSTRI MANUFAKTUR INDONESIA: SISTEMATIK KAJIAN LITERATUR - Hibarkah Kurnia; Sudarmono; Alvia Dwi Wahyuni; Nurmala Adistyani; Asep Arwan Sulaeman (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2023)
Material processing techniques in the manufacturing industry in Indonesia are more dominant in using metal applications as the main raw material in product design in the form of machines. The use of metal materials needs to be studied because before they are used in the industry, their designation must be known first so that these materials can be optimized in their use. The process of processing metal materials must pay attention to their type and properties in advance, especially in the process of forming and behavior during use. So that in its application it can be following the specifications of raw materials in a product that is produced. This study aims to find out and identify how important the role of metal materials is in their application in the world of the Indonesian manufacturing industry. This research method uses a systematic literature review method by collecting 20 articles related to the use of metal materials in various manufacturing industries from several national journals on the Google Scholar database. This research found several dominant articles published in 2020 and focused on the alloy casting industry. The results obtained from the collected data are that the use of metal materials plays an important role in the manufacturing industry in Indonesia. Metal materials are still very much needed as one of the main raw materials in the manufacturing industry because these materials have unique properties that non-metallic materials do not have